Coach Foucault: problematizing endurance running coaches' practices - Mills, J. P.; Denison, J. (Sports Coaching Review, 2013)
According to conventional thinking in endurance running, the more coaches can control athletes' training the more likely they are to be successful. However, the understanding that there may be numerous unintended consequences brought on by coaches' attempts to control their athletes' training is rarely acknowledged. In this paper, we draw on Michel Foucault's articulation of disciplinary power to examine how endurance running coaches' knowledge and understanding of how to plan their athletes' training has been constructed and generated, and what effect this has on: (1) endurance running coaches' understanding of how to coach; and (2) the making of the endurance running body. Our analysis was based on interviews with and observations on 15 high-performance male endurance coaches in the UK and the US. Our empirical material revealed an emphatic uptake of a range of disciplinary techniques by the participants, which, as discussed, can be at odds with the goals of successful competitive running. Thus, through Foucault's disciplinary lens we identified a series of disconnections and unintended consequences between the aims and effects of contemporary endurance training practices that can collectively undermine coaches' effectiveness.